Ten-year outcomes in first episode psychotic major depression patients compared with schizophrenia and bipolar patients - Heslin, M.; Lappin, J.M.; Lomas, B.; Reininghaus, U.; Onyejiaka, A.; Croudace, T.; Jones, P.B.; Murray, R.M.; Fearon, P.; Doody, G.A.; Dazzan, P.; Craig, T.J.; et al. (Elsevier, 2016)
We aimed to investigate long-term outcomes in psychotic major depression patients compared to schizophrenia and bipolar/manic psychosis patients, in an incidence sample, while accounting for diagnostic change. Based on Aetiology and Ethnicity in Schizophrenia and Other Psychoses (/ESOP and /ESOP-10), a first episode psychosis cohort was followed-up 10 years after first presentation. The Schedules for Clinical Assessment in Neuropsychiatry, WHO Life Chart and Global Assessment of Functioning were used to assess clinical, social and service use outcomes. Seventy-two PMD patients, 218 schizophrenia patients and 70 psychotic bipolar disorder / mania patients were identified at baseline. Differences in outcome between PMD and bipolar patients based on baseline and lifetime diagnosis were minimal. Differences in clinical, social and service use outcomes between PMD and schizophrenia were more substantial with PMD patients showing better outcomes on most variables. However, there was some weak evidence (albeit not quite statistically significant at p < 0.05) based on lifetime diagnoses that PMD patients were more likely to attempt suicide (OR 2.31, CI 0.98-5.42, p0.055) and self-harm (OR 2.34, CI 0.97-5.68, p0.060). PMD patients have better social and service use outcomes compared to people with schizophrenia, but may be more likely to attempt suicide or self-harm. This unique profile is important for clinicians to consider in any risk assessment.